Pengaruh Corporate Governance dan Cross-listing terhadap Kualitas Pengungkapan ESG: Studi pada Perusahaan Sektor Energi dan Bahan Baku yang Terdaftar di BEI 2019-2023 (International Forum of Researchers and Lecturers, 2025)
Corporate Governance and Cross-listing are considered crucial factors in promoting corporate transparency and accountability, particularly in sustainability reporting based on Environmental, Social, and Governance (ESG) standards. A strong governance structure is believed to enhance the quality of ESG disclosure, while Cross-listing serves as an external pressure that reinforces a company's commitment to global reporting standards. This study aims to examine the influence of board size, board independence, institutional ownership, audit committee size, and Cross-listing status on the quality of ESG disclosure. The research focuses on companies in the energy and basic materials sectors listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, using ESG data sourced from Bloomberg. The sample consists of 18 companies with a total of 73 observations selected through purposive sampling. Hypotheses were tested using multiple linear regression analysis. The results show that board size, board independence, institutional ownership, and Cross-listing have a positive and significant effect on the quality of ESG disclosure. Conversely, audit committee size has a negative and significant effect. These findings indicate that both internal pressure through governance mechanisms and external pressure through Cross-listing on foreign exchanges play an important role in driving the quality of corporate ESG disclosure.